Prevalencia de infecciones por geohelmintos en comunidades brasileñas: Uma revisão sistemática - Moreira Mesquita, Cristiane Aparecida; Almeida Torquete, Mariana; Paiva Barçante, Joziana Muniz; Barçante, Thales Augusto; Guimarães, Antônio Marcos; Rocha, Christiane (Spei Domus, 2021)
Introduction: Geo-helmintiasis are recognized due to their high morbidity and because they cause thousands of deaths annually, mainly of children in underdeveloped countries. There is a global proposal with a goal to be achieved, knowledge of the prevalence of geo-helminthiasis is essential. Even so, it is possible to assess the regions should receive greater attention in the search for treatment and control. The objective of this study is to evaluate the prevalence of infections due to geo helminthiasis in Brazil based on the analysis of the published literature. Methodology: For this, a systematic review of articles in PubMed, Scopus and Science Direct databases was made considering studies in which parasitological copro examinations were performed between 1/1/2010 and 8/17/2020. Studies representing the following data were included: number of participants, age group, parasi-tological method, geographic location. A total of 25 studies were identified with reports of prevalence in rural communities, indigenous school children, urban and peri urban areas. The studies were carried out in twelve Brazilian states in the South, South West and North West region. Results: 56% of the studies included individuals aged 0 to 93 years. The techniques base on spontaneous sedimentation were the most used. Ascaris lumbricoides was another species found (0,15 to 48,8%), followed by Trichuris trichiura (0,16 to 61,5%) and hookworns (0,08 to 22,8%). The state of Rio Grande do sul (RS), Minas Gerais (MG), Paraná (PR), Alagoas (AL) and Bahia (BA) had higher reports (>20%) of Ascaris lumbricoides and it also represented reports for T. trichiura (PR, AL and BA) and hookworms (MG, AL and BA). Conclusion: In Brazil, studies on the prevalence of soil transmitted helminth infections are scarce, mainly in regions of extreme poverty, the published works do not refer to the prevalence of municipalities and of certain communities, which doesn’t not always represent the reality of the local. More studies on the prevalence of infections due to soil transmitted helminth infections are necessary to know areas of greater risk where the measures for treatment and control should be more effective